Geography and the Paris Academy of Sciences: politics and patronage in early 18th-century France - Heffernan, Michael (Wiley, 2014)
This essay considers the politics and patronage of geography in early-modern France. It examines how the Paris Academy of Sciences, widely acknowledged as the 18th century’s pre-eminent scientific society, came to recognise geography as an independent science in 1730, a century before the establishment of the first geographical societies. Although the Academy was centrally concerned with cartography from its inception in 1666, it initially afforded no official status to geography, which was viewed either as a specialised form of historical inquiry or as a minor component within the hegemonic science of astronomy. The rise of Newtonian mathematics and the associated controversy about the shape of the earth challenged the Academy’s epistemological foundations and prompted a debate about the educational and political significance of geography as a scientific practice. The death in 1726 of Guillaume Delisle, a prominent Academy astronomer-cartographer and a popular geography tutor to the young Louis XV, led to a spirited campaign to elect Philippe Buache, Delisle’s protege, to a new Academy position as a geographer rather than an astronomer. The campaign emphasised the social and political utility of geography, though the Academy’s decision to recognise this new and distinctively modern science was ultimately facilitated by traditional networks of patronage within the French Royal Court.